2023
DOI: 10.1021/acscatal.3c02224
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Controlled Palladium-Catalyzed Decarboxylative Heck Coupling for Regioselective Access to Branched Olefins

Abstract: A highly chemo-and regioselective decarboxylative Heck-type coupling of carboxylic acids and terminal olefins has been developed using a catalytic system composed of Pd(OAc) 2 in the presence of phosphine-sulfonamido ligands. Using the bulky ligand L1 leads to high selectivity for 1,1-disubstituted (branched; b) olefins that are generally difficult to obtain. The influence of all relevant reaction parameters was evaluated using a combination of design of experiments and one factor at a time optimization. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…DFT calculations uncovered a favorable π–π interaction between the styrene group and the P Ph 2 N ArCF3 2 ligand, which could explain its preference for the linear pathway. Conversely, the bulky P t Bu 2 N ArCF3 2 ligand destabilizes this pathway due to steric hindrance, inverting the regiochemical outcome . P 2 N 2 s are well-known to be powerful ligands, particularly due to the flexible, basic nitrogen atoms in the ligand’s second-coordination sphere, enabling H 2 splitting and related transformations .…”
Section: Discussionmentioning
confidence: 99%
“…DFT calculations uncovered a favorable π–π interaction between the styrene group and the P Ph 2 N ArCF3 2 ligand, which could explain its preference for the linear pathway. Conversely, the bulky P t Bu 2 N ArCF3 2 ligand destabilizes this pathway due to steric hindrance, inverting the regiochemical outcome . P 2 N 2 s are well-known to be powerful ligands, particularly due to the flexible, basic nitrogen atoms in the ligand’s second-coordination sphere, enabling H 2 splitting and related transformations .…”
Section: Discussionmentioning
confidence: 99%
“…The choice of B97D3-BJ functional stemmed from its computational efficiency and its consistency with our prior research on metal–ligand complexes, aligning well with experimental findings. 13,55,56 However, we also conducted a comparative study involving other DFT functionals for the critical intermediates (TDI) and transition states (TDTS), which are mentioned in detail in the ESI (Fig. S1†).…”
Section: Computational Details and General Approachmentioning
confidence: 99%
“…One must note, however, that it cannot be excluded completely, that unexpected side reactions may be accessible in an experimental system which might not have been envisioned or possibly overlooked in the prior computational work. Computational studies of this kind have demonstrated their potential to narrow down significantly the plethora of choices an experimentalist could make with the potential of predictive catalyst design for example for olefin hydrogenation, 16 decarboxylative Heck-type coupling 13 and direct insertion of CO 2 14,15 into arenes.…”
Section: Computational Details and General Approachmentioning
confidence: 99%
See 1 more Smart Citation